Adolescents in The City: Rebellion and Inconformism in Peruvian Modern Narrative - Susti, Alejandro (2021)
This article examines two narrative texts published in Peru during the sixties: Los inocentes. Relatos de collera ([1961] 2011) by Oswaldo Reynoso (1932-2016), and Los cachorros (1967) by Mario Vargas Llosa. The analysis focuses on the construction of identities among the adolescent subjects who star in them, considering elements such as social class, generation, gender, territory, language and others, as part of the emergence of the so-called “youth cultures” in western societies since the fifties. In addition, it recognizes the differences between both narratives in terms of the representation of youth cultures, particularly with respect to the relationship that adolescent subjects establish with hegemonic culture.